Guinea : Poverty Reduction Strategy Paper-Progress Report. (IMF Staff Country Reports; Country Report, 2012)
Poverty Reduction Strategy Papers (PRSPs) are prepared by member countries in broad consultation with stakeholders and development partners, including the staffs of the World Bank and the IMF. Updated every three years with annual progress reports, they describe the country's macroeconomic, structural, and social policies in support of growth and poverty reduction, as well as associated external financing needs and major sources of financing. This country document for Guinea, dated May 2012 is being made available on the IMF website by agreement with the member country as a service to users of the IMF website.